Students’ Metacognitive Awareness in Natural Science Learning: An Overview by Gender - Muhammad Asy'ari; Baiq Mirawati; Siti Zubaidah; Susriyati Mahanal (Postgraduate, University of Mataram, 2022)
This study aimed to identify the metacognitive awareness of high school students in natural science learning based on gender. This research is a descriptive study with a sample of 24 students. Data on students' metacognition awareness was collected using the Metacognition Awareness Inventory (MAI) which was analyzed descriptively and statistically. The results showed that students' metacognitive awareness was categorized as good enough (1.33 < MA ≤ 2.33) and low (MA ≥ 1.33). Students' metacognition awareness was not significantly different in terms of gender (p> 0.05). Based on the results of the study, it can be concluded that metacognitive awareness needs to be improved through good interventions in learning. Student gender differences need to be investigated further using a larger sample to obtain more relevant and comprehensive data on metacognitive awareness